Hidden Enemy - Hardcastle, Michael (Methuen Children's Books Ltd, 1986)
Boy Soldier Roger Todturn is kidnapped on a cross country runs after his father has won a fortune on the football Pools.
Keywords: Juvenile literature-Friendships-Kidnapping-Fiction